Aid for Trade, Export Product Diversification and Import Product Diversification - Sèna Kimm Gnangnon (ZBW – Leibniz Information Centre for Economics, 2020)
The literature on the effect of Aid for Trade (AfT) has shown that AfT flows can be associated with greater export product diversification in recipient-countries. However, the import product diversification effect of AfT interventions has received scant attention in this literature. The present article aims to fill this gap in the literature by investigating the effect of AfT flows on import product diversification, including when countries diversify their export product baskets. The empirical analysis has shown that AfT flows are associated with greater import product diversification in countries that diversify their export product baskets. This finding applies both to total AfT flows and to its three major components, namely AfT flows for economic infrastructure, AfT flows for productive capacity, and AfT flows for trade policy and regulation. Additionally, the magnitude of the positive effect of total AfT flows on import product diversification increases as recipient-countries enjoy a convergence of their export product structure towards the world's export product structure. On another note, the empirical analysis has revealed that AfT flows induce greater import product diversification in countries that further liberalize their trade policies. These results have important policy implications for both donors and recipient-countries.
Keywords: F35; F14; 330; Aid for Trade; Export Product Diversification; Import Product Diversification